Efektivitas Restorative Justice sebagai Alternatif Penyelesaian Tindak Pidana Anak dalam Hukum Pidana Indonesia - Mahfud Rahmadani; Karli Karli (Decisio: Jurnal Ilmiah Hukum, 2025)
Restorative justice has emerged as an alternative approach in resolving juvenile criminal cases, emphasizing reconciliation rather than punitive measures. In Indonesia, the implementation of restorative justice is legally supported through Law No. 11 of 2012 on the Juvenile Criminal Justice System, which mandates diversion as a primary mechanism. However, despite its progressive framework, various challenges hinder the effective application of restorative justice in practice. These obstacles include inconsistencies in law enforcement, limited institutional support, and societal resistance to non-punitive legal resolutions. This study employs a qualitative method with a normative legal approach, focusing on regulatory analysis and the interpretation of legal norms in current practices. Data were collected through comprehensive literature reviews, classifying legal materials into primary, secondary, and tertiary sources. The findings indicate that restorative justice, particularly through diversion, provides a more humane resolution for juvenile offenders, reducing stigmatization and enhancing rehabilitation efforts. However, disparities in law enforcement practices, lack of adequate facilities, and varying levels of community acceptance have impeded its full implementation. Strengthening legal frameworks, increasing capacity-building programs for law enforcement, and enhancing public awareness are essential for the optimal application of restorative justice in Indonesia. Effective collaboration between legal institutions and community-based organizations is crucial in ensuring a fair and rehabilitative justice system for juvenile offenders.